Proficiency tests for soil analysis services via proximal sensing - Tiago R. Tavares; José A.M. Demattê; Abdul M. Mouazen; Eyal Ben-Dor; Adriano A. Anselmi; Victor Monseff de A. Campos; Budiman Minasny; Sérgio H. Godinho Silva; Sabine Chabrillat; Konstantinos Karyotis; Heitor Cantarella; Cristiano A. Andrade; et al. (Geoderma)
Soil Spectral Libraries (SSL) and spectroscopy-based methods using varied regions of the electromagnetic spectrum for direct soil analysis are rapidly gaining traction in agricultural and environmental applications. However, the absence of standardized tests, specifically designed for these new methods, prompts concerns about performance consistency and transparency in the marketplace. This discussion paper underscores the critical factors that influence predictive performance and stresses the need for proficiency tests tailored to sensor-based techniques. It also highlights the significance of error metrics for accurate interpretation. Establishing robust proficiency tests is crucial for ensuring reliable soil analysis services and promoting the adoption of best practices in this technology.